Thorough investigation of a canine autoinflammatory disease (AID) confirms one main risk locus and suggests a modifier locus for amyloidosis. - Mia Olsson (Public Library of Science (PLoS), 2013)
Autoinflammatory disease (AID) manifests from the dysregulation of the innate immune system and is characterised by systemic and persistent inflammation. Clinical heterogeneity leads to patients presenting with one or a spectrum of phenotypic signs, leading to difficult diagnoses in the absence of a clear genetic cause. We used separate genome-wide SNP analyses to investigate five signs of AID (recurrent fever, arthritis, breed specific secondary dermatitis, otitis and systemic reactive amyloidosis) in a canine comparative model, the pure bred Chinese Shar-Pei. Analysis of 255 DNA samples revealed a shared locus on chromosome 13 spanning two peaks of association. A three-marker haplotype based on the most significant SNP (p<2.6×10(-8)) from each analysis showed that one haplotypic pair (H13-11) was present in the majority of AID individuals, implicating this as a shared risk factor for all phenotypes. We also noted that a genetic signature (F ST) distinguishing the phenotypic extremes of the breed specific Chinese Shar-Pei thick and wrinkled skin, flanked the chromosome 13 AID locus; suggesting that breed development and differentiation has played a parallel role in the genetics of breed fitness. Intriguingly, a potential modifier locus for amyloidosis was revealed on chromosome 14, and an investigation of candidate genes from both this and the chromosome 13 regions revealed significant (p<0.05) renal differential expression in four genes previously implicated in kidney or immune health (AOAH, ELMO1, HAS2 and IL6). These results illustrate that phenotypic heterogeneity need not be a reflection of genetic heterogeneity, and that genetic modifiers of disease could be masked if syndromes were not first considered as individual clinical signs and then as a sum of their component parts.